Prevalence of dengue risk factors in patients treated for Diabetes Mellitus at a hospital in Mexico - Piedra-Robles, José; Diaz-Morales, Jennifer; Baldovinos-Leyva, Irma (Revista Acciones Médicas, 2024)
The spread of vector-borne diseases facilitates the connection between dengue and diabetes, with patients showing a predisposition to severe complications such as nephropathy, cardiovascular problems, altered coagulation, and thrombocytopenia, which are markedly manifest in them. This situation led to a study at the Naval Hospital in Acapulco, aimed at determining the level of dengue risk factors in diabetic patients; using a descriptive methodology, through simple random sampling, detailing information on results conducted on 100 patients; revealing that diabetics have a favorable predisposition to develop severe dengue, providing a basis for understanding the complex interaction between dengue and diabetes, in addition to highlighting the need to implement preventive and integrated management strategies. It is important to establish treatment and prevention protocols for diabetic individuals in risk environments, as well as to develop and apply specific preventive and management strategies to mitigate risks and improve their health conditions.
Keywords: glycemic control; dengue; diabetes; incidence